Missing Links : Gender Equity in Science and Technology for Development. (International Development Research Centre, 1995)
In this landmark book, the UN-commissioned Gender Working Group outlines its policy proposals for national science and technology programs. Its goal is to ensure that women and men have equal access to and benefit equally from science and technology. The proposals are supported by essays written by distinguished scholars and experts.